Unconventional Builders - Van Dine, Alan (J.G. Ferguson Publishing Company, 1977)
Sir Christopher Whren -- Ireland's Curious Towers -- E-temen-anki -- Desing for the Haunted House -- Machu Picchu -- The Cuckoo Construction Company -- Petra -- High Gothic -- The great wall of China -- Igloos -- Heorot -- The trouble with cabins and cottages -- The first houses -- Fouquet's only -- Shakespeare's playhouse -- Jericho -- The fallen idol